Penerapan Algoritma Iterative Dichotomiser 3 (ID3) Dalam Penentuan Penerima Program Bantuan Dana UMKM Kabupaten Labuhanbatu - Hariani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Micro, small and medium enterprises (MSMEs) play an important role in economic development because of the relatively high level of labor absorption and small capital requirements for investment. The low level of investment and the low growth of new businesses in Indonesia need serious attention in the future in order to develop Micro, Small and Medium Enterprises (MSMEs) towards highly competitive businesses. Seeing this, researchers are interested in conducting research by applying the Interative Dichotomiser 3 (ID3) Algorithm method to determine the receipt of MSME funding assistance in an application of this algorithm.